Plated steel sheet

By crystallizing the surface -shaped MG2Si phase on the surface of the plating steel plate, the problem of insufficient end facial corrosion resistance in the existing technology is solved, and the plating plane plane and end surface corrosion resistance are achieved.

CN119365624AActive Publication Date: 2025-01-24NIPPON STEEL CORPORATION
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202380047405.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-22
Filing Date
2023-06-19
Publication Date
2025-01-24
Estimated Expiration
2043-06-19

AI Technical Summary

Technical Problem

The prior art is difficult to improve the end surface corrosion resistance of the plated steel plate without sacrificing the corrosion resistance of the plated steel plate.

Method used

By adjusting the manufacturing conditions of the coating, a large number of needle-like Mg2Si phases are crystallized on the surface of the coating, so that the Mg2Si phase is corroded in the early stages of corrosion and Mg ions are generated to protect the end surface of the steel plate.

Benefits of technology

It is achieved that the end-face corrosion resistance of the coated steel plate is significantly improved without damaging the plane corrosion resistance of the coating, taking into account both the plane and end-face corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005189865880000191
    Figure BDA0005189865880000191
  • Figure BDA0005189865880000201
    Figure BDA0005189865880000201
  • Figure BDA0005189865880000211
    Figure BDA0005189865880000211
Patent Text Reader

Abstract

This plated steel sheet is provided with a steel sheet and a plating layer disposed on the surface of the steel sheet, the chemical composition of the plating layer containing, in mass%, 10.0-25.0% of Al, 3.0-10.0% of Mg, 0.01-2.0% of Fe, more than 0% but not more than 2.0% of Si, the remainder containing Zn and impurities, and the number density of Mg2Si phases having a major axis of 2 [mu] m or more exposed on the surface of the plating layer being 3-150 per 10000 [mu] m2 area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a plated steel sheet.

[0002] This application claims priority based on Japanese Patent Application No. 2022-100351 filed in Japan on June 22, 2022, and the contents of which are incorporated herein by reference. Background Art

[0003] Zn-Al-Mg hot-dip plated steel sheets having a hot-dip Zn plating layer containing Al and Mg have excellent corrosion resistance and are therefore widely used as materials for structural members requiring corrosion resistance, such as building materials.

[0004] For example, Patent Document 1 describes a plated steel material comprising a steel material and a plating layer comprising a Zn-Al-Mg alloy layer disposed on the surface of the steel material, wherein the Zn-Al-Mg alloy layer has a Zn phase and contains a Mg-Sn intermetallic compound phase in the Zn phase, and the plating layer has the following chemical composition: in terms of mass %, it contains Zn: more than 65.0%, Al: more than 5.0% and less than 25.0%, Mg: more than 3.0% and less than 12.5%, Sn: 0.1% to 20.0%, and impurities, and satisfies the following Formulas 1 to 5.

[0005] Formula 1: Bi+In <Sn

[0006] Formula 2: Y+La+Ce≤Ca

[0007] Formula 3: Si <Sn

[0008] Formula 4: O≤Cr+Ti+Ni+Co+V+Nb+Cu+Mn<0.25

[0009] Formula 5: O≤Sr+Sb+Pb+B<0.5

[0010] Patent document 2 describes a plated steel material, which comprises a steel material and a plating layer arranged on the surface of the steel material and comprising a Zn-Al-Mg alloy layer, wherein in a cross section of the Zn-Al-Mg alloy layer, the area fraction of the MgZn2 phase is 45 to 75%, the combined area fraction of the MgZn2 phase and the Al phase is 70% or more, and the area fraction of the Zn-Al-MgZn2 ternary eutectic structure is 0 to 5%, and the plating layer has the following chemical composition: in terms of mass %, it comprises Zn: more than 44.90% and less than 79.90%, Al: more than 15% and less than 35%, Mg: more than 5% and less than 20%, Ca: more than 0.1% and less than 3.0%, and impurities When element group A is set to Y, La and Ce, element group B is set to Cr, Ti, Ni, Co, V, Nb, Cu and Mn, element group C is set to Sr, Sb and Pb, and element group D is set to Sn, Bi and In, the total content of elements selected from element group A is 0% to 0.5%, the total content of Ca and elements selected from the above element group A is 0.1% or more and less than 3.0%, the total content of elements selected from element group B is 0% to 0.25%, the total content of elements selected from element group C is 0% to 0.5%, and the total content of elements selected from element group D is 0% to 20.00%.

[0011] Patent document 3 describes a hot-dip Al-Zn-Mg-Si steel plate having a plated film on the surface of the steel plate, wherein the plated film includes an interface alloy layer present at the interface with the base steel plate and a main layer present on the alloy layer, containing 25 to 80 mass % of Al, more than 0.6 mass % and less than 15 mass % of Si, and more than 0.1 mass % and less than 25 mass % of Mg, and the area ratio of Mg2Si at the surface of the main layer is more than 10%.

[0012] In recent years, hot-dip galvanized steel materials for building materials used in roofs, wall materials, etc. require both the corrosion resistance of the coating itself, i.e., flat surface corrosion resistance, and the corrosion resistance of the cut end surface, i.e., end surface corrosion resistance. On the other hand, a technology that achieves both flat surface corrosion resistance and end surface corrosion resistance at a high level has not been studied.

[0013] Prior art literature

[0014] Patent Literature

[0015] Patent Document 1: International Publication No. 2018 / 139619

[0016] Patent Document 2: International Publication No. 2018 / 139620

[0017] Patent Document 3: Japanese Patent Application Publication No. 2016-166414 Summary of the invention

[0018] Problems to be solved by the invention

[0019] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a plated steel sheet having excellent both flat surface corrosion resistance and edge surface corrosion resistance.

[0020] Means for solving problems

[0021] In order to solve the above-mentioned problems, the present invention adopts the following configuration.

[0022] [1] A plated steel sheet comprising a steel sheet and a plating layer disposed on a surface of the steel sheet,

[0023] The chemical composition of the above-mentioned coating contains, by mass%, the following:

[0024] Al: 10.0-25.0%,

[0025] Mg: 3.0-10.0%,

[0026] Fe: 0.01-2.0%,

[0027] Si: more than 0% and 2.0% or less,

[0028] further comprising one or more selected from the following Group A, Group B, and Group C,

[0029] The remainder contains Zn and impurities.

[0030] The number density of the Mg2Si phase with a major diameter of 2 μm or more exposed on the surface of the above-mentioned coating layer is 2 The area is 3 to 150.

[0031] [Group A]Ni: 0~1.0%

[0032] [Group B] Ca: 0~0.05%

[0033] [Group C] Sb: 0-0.5%, Pb: 0-0.5%, Cu: 0-1.0%, Sn: 0-1.0%, Ti: 0-1.0%, Cr: 0-1.0%, Nb: 0-1.0%, Zr: 0-1.0%, Mn: 0-1.0%, Mo: 0-1.0%, Ag: 0-1.0%, Li: 0-1.0%, La: 0-0.5%, Ce: 0-0.5%, B: 0-0.5%, Y: 0-0.5%, P: 0-0.5%, Sr: 0-0.5%, Co: 0-0.5%, Bi: 0-0.5%, In: 0-0.5%, V: 0-0.5%, W: 0-0.5% or more: 0-5% in total

[0034] [2] The plated steel sheet according to [1], wherein the chemical composition of Mg and Si in the plating layer is Mg: 4.5 to 8 mass %, Si: 0.1 to 2 mass %,

[0035] The number density of the Mg2Si phase with a major diameter of 2 μm or more exposed on the surface of the above-mentioned coating layer is 2 The area is 15 to 150.

[0036] [3] The plated steel sheet according to [1], wherein the chemical composition of Al, Mg and Si in the plating layer is Al: 15-25 mass %, Mg: 4.5-8 mass %, Si: 0.1-2 mass %,

[0037] The number density of the Mg2Si phase with a major diameter of 2 μm or more exposed on the surface of the above-mentioned coating layer is 2 The area is 30 to 150.

[0038] [4] The plated steel sheet according to any one of [1] to [3], wherein the chemical composition of the coating layer is Al: 15-25 mass %, Mg: 4.5-8 mass %, Si: 0.1-2 mass %,

[0039] The number density of the Mg-Si-Zn-Al phase with a major diameter of 2 μm or more exposed on the surface of the plating layer is 2 The area is 5 to 150.

[0040] [5] A plated steel sheet according to any one of [1] to [3], wherein the chemical composition of the coating layer contains Sn: 0.05 to 0.5 mass %, and in an X-ray diffraction measurement of the coating layer, a Mg2Sn phase is detected in the coating layer.

[0041] [6] The plated steel sheet according to [4], wherein the chemical composition of the coating layer contains Sn: 0.05 to 0.5 mass %, and in an X-ray diffraction measurement of the coating layer, a Mg2Sn phase is detected in the coating layer.

[0042] [7] The plated steel sheet according to [1], wherein the plating layer has a chemical composition containing the group A in terms of mass %.

[0043] [8] The plated steel sheet according to [1], wherein the plating layer has a chemical composition containing the group B in mass %.

[0044] [9] The plated steel sheet according to [1], wherein the plating layer has a chemical composition containing the group C in mass %.

[0045] Effects of the Invention

[0046] According to the above-described aspects of the present invention, it is possible to provide a plated steel sheet having excellent both plane corrosion resistance and edge corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is a schematic cross-sectional view of a hot-dip plated steel material as an embodiment of the present invention. DETAILED DESCRIPTION

[0048] The plated steel sheet is cut so that the end face of the steel sheet is exposed at the cut end face of the plated steel sheet. The corrosion resistance of the end face of the steel sheet (hereinafter referred to as end face corrosion resistance) is generally achieved by the following operation. That is, it is achieved by forming a coating containing an element (such as Zn, Mg, etc.) with a higher ionization tendency than the base metal as a coating on the surface of the steel sheet, generating corrosion products by causing the coating to corrode preferentially relative to the base metal, and using the corrosion products to protect the end face of the steel sheet from corrosion. Therefore, the improvement of the end face corrosion resistance brought about by the coating is not compatible with the improvement of the corrosion resistance of the coating itself, that is, the improvement of the plane corrosion resistance.

[0049] Therefore, the inventors of the present invention have conducted in-depth research to improve both the flat corrosion resistance and the end corrosion resistance of the coating containing Al and Mg. In the coating containing Al, Mg, Si and Zn, there is a possibility that the Mg2Si phase is included. The Mg2Si phase contains a relatively large amount of Mg that can contribute to the corrosion resistance of the end face of the steel plate, but the Mg2Si phase of the conventional plated steel plate is mostly present inside the coating, especially in the area close to the interface with the steel plate, and its shape is roughly block-shaped. Therefore, in the early stage of corrosion of the coating, the Mg2Si phase is not affected by corrosion.

[0050] However, the inventors of the present invention conducted intensive research and succeeded in crystallizing a relatively large number of needle-shaped Mg2Si phases on the surface of the coating by adjusting the manufacturing conditions of the coating. The presence of a large number of Mg2Si phases on the surface of the coating causes the Mg2Si phases to corrode from the initial stage of corrosion of the coating. As the Mg2Si phases corrode, Mg ions are generated as corrosion products, and the Mg ions protect the end face of the steel sheet from corrosion. In this way, the corrosion resistance of the end face is successfully improved.

[0051] In addition, since there are a large number of Mg2Si phases on the surface of the coating, the end face corrosion resistance can be improved by the corrosion products of the Mg2Si phase from the initial stage of corrosion. Therefore, the end face corrosion resistance can be improved without sacrificing the planar corrosion resistance of the coating, thereby achieving a balance between the planar corrosion resistance and the end face corrosion resistance of the coating.

[0052] Hereinafter, a plated steel sheet as an embodiment of the present invention will be described.

[0053] The plated steel sheet of the present embodiment comprises a steel sheet and a plating layer disposed on the surface of the steel sheet, wherein the chemical composition of the plating layer comprises, by mass%, Al: 10.0-25.0%, Mg: 3.0-10.0%, Fe: 0.01-2.0%, Si: more than 0% and less than 2.0%, and further comprises one or more selected from the following Group A, Group B, and Group C, and the remainder comprises Zn and impurities, and the number density of the Mg2Si phase with a long diameter of 2 μm or more exposed on the surface of the plating layer is 2 3 to 150.

[0054] [Group A]Ni: 0~1.0%

[0055] [Group B] Ca: 0~0.05%

[0056] [Group C] Sb: 0-0.5%, Pb: 0-0.5%, Cu: 0-1.0%, Sn: 0-1.0%, Ti: 0-1.0%, Cr: 0-1.0%, Nb: 0-1.0%, Zr: 0-1.0%, Mn: 0-1.0%, Mo: 0-1.0%, Ag: 0-1.0%, Li: 0-1.0%, La: 0-0.5%, Ce: 0-0.5%, B: 0-0.5%, Y: 0-0.5%, P: 0-0.5%, Sr: 0-0.5%, Co: 0-0.5%, Bi: 0-0.5%, In: 0-0.5%, V: 0-0.5%, W: 0-0.5% or more: 0-5% in total

[0057] In the following description, the "%" expression of the content of each element of the chemical composition means "mass %". The content of the elements of the chemical composition is sometimes recorded as element concentration (for example, Zn concentration, Mg concentration, etc.). "Plane corrosion resistance" means the property of the coating (specifically, the Zn-Al-Mg alloy layer) itself not being easily corroded. "End surface corrosion resistance" means the property of suppressing the corrosion of the steel plate at the exposed part of the steel plate (for example, the cut end surface of the plated steel plate). "Coating" refers to a plating film produced by the so-called hot dip plating process.

[0058] like Figure 1 As shown in , the plated steel sheet 1 of the present embodiment has a steel sheet 11. There is no particular limitation on the shape of the steel sheet 11. In addition, the steel sheet 11 may be a base steel sheet formed into a steel pipe, civil engineering materials (gutters, corrugated pipes, gutter covers, anti-sand plates, bolts, metal meshes, guardrails, waterproof walls, etc.), home appliance components (frames of outdoor units of air conditioners, etc.), automobile parts (travel components, etc.), etc. The forming process may be, for example, various plastic processing methods such as pressing, roll forming, and bending.

[0059] There is no particular restriction on the material of the steel plate 11. The steel plate 11 can be, for example, various steel plates such as general steel, Al-killed steel, ultra-low carbon steel, high carbon steel, various high-tensile steels, and some high-alloy steels (steel containing strengthening elements such as Ni and Cr). The steel plate 11 can also be a hot-rolled steel plate, hot-rolled steel strip, cold-rolled steel plate, and cold-rolled steel strip described in JIS G 3302: 2010. There is no particular restriction on the manufacturing method of the steel plate (hot rolling method, pickling method, cold rolling method, etc.) and its specific manufacturing conditions.

[0060] As described below, a steel sheet 11 with adjusted surface roughness is used for the steel sheet to be plated original sheet. The surface roughness of the steel sheet can be adjusted, for example, by setting the surface of the roller or the roller for skin pass rolling to a predetermined surface roughness, transferring the surface shape of the roller during rolling or skin pass rolling, etc.

[0061] The plated steel sheet 1 of the present embodiment has a coating 12 disposed on the surface of a steel sheet 11. The coating 12 of the plated steel sheet 1 of the present embodiment is mainly composed of a Zn-Al-Mg alloy layer due to the chemical composition described later. In addition, the coating 12 of the plated steel sheet 1 of the present embodiment may also include an interface alloy layer having Fe and Al as main components between the steel sheet 11 and the Zn-Al-Mg alloy layer. That is, the coating 12 may be a single-layer structure of a Zn-Al-Mg alloy layer, or a laminated structure including a Zn-Al-Mg alloy layer and an interface alloy layer.

[0062] The chemical composition of the coating of the present embodiment is composed of Zn and other alloying elements. The chemical composition of the coating is described in detail below. It should be noted that the elements whose lower limit of concentration is described as 0% are optional elements, which are not necessary to solve the problem of the plated steel sheet of the present embodiment, but are allowed to be included in the coating for the purpose of improving the characteristics.

[0063] <Al:10.0~25.0%>

[0064] Al contributes to the improvement of plane corrosion resistance, end face corrosion resistance and processability. Therefore, the Al concentration is set to 10.0% or more. The Al concentration can also be set to 11.0% or more, 12.0% or more, or 15.0% or more. On the other hand, in the case of excessive Al, the Mg concentration and the Zn concentration are relatively reduced, and the end face corrosion resistance deteriorates. Therefore, the Al concentration is set to 25.0% or less. The Al concentration can also be set to 24.0% or less, 22.0% or less, or 20.0% or less.

[0065] <Mg:3.0~10.0%>

[0066] Mg is an element necessary to ensure planar corrosion resistance and end face corrosion resistance. In addition, it is also necessary to crystallize the Mg2Si phase. Therefore, the Mg concentration is set to 3.0% or more. The Mg concentration can also be set to 4.0% or more, 5.0% or more, or 6.0% or more. On the other hand, if the Mg concentration is excessive, the workability, especially the powdering property, may deteriorate, and further the planar corrosion resistance may deteriorate. Thus, the Mg concentration is set to 10.0% or less. The Mg concentration can also be set to 8.0% or less or 7.0% or less.

[0067] <Fe: 0.01% to 2.0%>

[0068] The concentration of Fe can also be 0%, but Fe can also be contained in the coating at 0.01% or more. It has been confirmed that if the Fe concentration is 2.0% or less, there is no adverse effect on the performance of the coating. The Fe concentration can also be set, for example, to 0.05% or more, 0.1% or more, 0.5% or more, or 1.0% or more. The Fe concentration is set to 2.0% or less. The Fe concentration can also be set to 1.8% or less or 1.5% or less. Since Fe may be mixed in from the base steel plate, the Fe concentration can also be 0.05% or more.

[0069] <Si: more than 0% and 2.0% or less>

[0070] Si helps to improve the planar corrosion resistance. In addition, it is also necessary to crystallize the Mg2Si phase. Therefore, the Si concentration can also be set to more than 0%, 0.01% or more, 0.02% or more, or 0.06% or more. On the other hand, if the Si concentration is excessive, the planar corrosion resistance and the end face corrosion resistance deteriorate. Therefore, the Si concentration is set to 2.0% or less. The Si concentration can also be set to 1.8% or less, 1.6% or less, 1.2% or less, or 1.0% or less.

[0071] Furthermore, the coating of the present embodiment may also contain one or more selected from the following Group A, Group B, and Group C.

[0072] [Group A] Ni: 0 to 1.0%

[0073] [Group B] Ca: 0 to 0.05%

[0074] [Group C] Sb: 0-0.5%, Pb: 0-0.5%, Cu: 0-1.0%, Sn: 0-1.0%, Ti: 0-1.0%, Cr: 0-1.0%, Nb: 0-1.0%, Zr: 0-1.0%, Mn: 0-1.0%, Mo: 0-1.0%, Ag: 0-1.0%, Li: 0-1.0%, La: 0-0.5%, Ce: 0-0.5%, B: 0-0.5%, Y: 0-0.5%, P: 0-0.5%, Sr: 0-0.5%, Co: 0-0.5%, Bi: 0-0.5%, In: 0-0.5%, V: 0-0.5%, W: 0-0.5% or more: 0-5% in total

[0075] <Ni:0~1.0%>

[0076] The concentration of Ni as group A may also be 0%. On the other hand, Ni contributes to the improvement of the end surface corrosion resistance. Therefore, the Ni concentration may be set to 0.05% or more, 0.08% or more, or 0.1% or more. On the other hand, if the Ni concentration is excessive, the flat corrosion resistance deteriorates. Therefore, the Ni concentration is set to 1.0% or less. The Ni concentration may also be set to 0.8% or less, 0.6% or less, or 0.5% or less.

[0077] <Ca:0%~0.05%>

[0078] The Ca concentration of group B may also be 0%. On the other hand, Ca is an element that can adjust the optimal Mg dissolution amount for imparting flat corrosion resistance. Therefore, the Ca concentration may also be 0.005% or more or 0.01% or more. On the other hand, if the Ca concentration is excessive, flat corrosion resistance and workability deteriorate. Therefore, the Ca concentration is set to 0.05% or less. The Ca concentration may also be set to 0.04% or less.

[0079] Furthermore, in the plating layer of the present embodiment, as group C, one or more elements selected from the group consisting of Sb: 0 to 0.5%, Pb: 0 to 0.5%, Cu: 0 to 1.0%, Sn: 0 to 1.0%, Ti: 0 to 1.0%, Cr: 0 to 1.0%, Nb: 0 to 1.0%, Zr: 0 to 1.0%, Mn: 0 to 1.0%, Mo: 0 to 1.0%, Ag: 0 to 1.0%, Li: 0 to 1.0%, La: 0 to 0.5%, Ce: 0 to 0.5%, B: 0 to 0.5%, Y: 0 to 0.5%, P: 0 to 0.5%, Sr: 0 to 0.5%, Co: 0 to 0.5%, Bi: 0 to 0.5%, In: 0 to 0.5%, V: 0 to 0.5%, and W: 0 to 0.5% may be contained. The total content of these elements is set to 0 to 5%. If the total content exceeds 5%, the flat surface corrosion resistance or the end surface corrosion resistance may be reduced.

[0080] <Sb and Pb: 0 - 0.5% respectively>

[0081] The concentrations of Sb and Pb can also be 0%. On the other hand, Sb and Pb contribute to the improvement of the end face corrosion resistance. Therefore, the concentrations of Sb and Pb can also be set to 0.05% or more, 0.10% or more, or 0.15% or more respectively. On the other hand, if the concentrations of Sb and Pb are excessive, the planar corrosion resistance deteriorates. Therefore, the concentrations of Sb and Pb are set to 0.5% or less. The concentrations of Sb and Pb can also be set to 0.4% or less, 0.3% or less, or 0.25% or less.

[0082] <Cu, Ti, Cr, Nb, Zr, Mn, Mo, Ag and Li: 0 - 1.0% respectively>

[0083] The concentrations of Cu, Ti, Cr, Nb, Zr, Mn, Mo, Ag and Li can also be 0% respectively. On the other hand, they contribute to the improvement of the end face corrosion resistance. Therefore, the concentrations of Cu, Ti, Cr, Nb, Zr, Mn, Mo, Ag and Li can also be set to 0.05% or more, 0.08% or more, or 0.10% or more respectively. On the other hand, if the concentrations of Cu, Ti, Cr, Nb, Zr, Mn, Mo, Ag and Li are excessive, the planar corrosion resistance deteriorates. Therefore, the concentrations of Cu, Ti, Cr, Nb, Zr, Mn, Mo, Ag and Li are set to 1.0% or less. The concentrations of Cu, Ti, Cr, Nb, Zr, Mn, Mo, Ag and Li can also be set to 0.8% or less, 0.7% or less, or 0.6% or less.

[0084] <Sn: 0 - 1.0%>

[0085] The Sn concentration can also be 0%. On the other hand, Sn is an element that forms an intermetallic compound with Mg and improves the end face corrosion resistance of the coating. Therefore, the Sn concentration can also be set to 0.05% or more, 0.1% or more, or 0.2% or more. However, if the Sn concentration is excessive, the planar corrosion resistance deteriorates. Therefore, the Sn concentration is set to 1.0% or less. The Sn concentration can also be set to 0.8% or less, 0.6% or less, or 0.5% or less.

[0086] <La, Ce, B, Y, P and Sr: 0 - 0.5% respectively>

[0087] The concentration of each of La, Ce, B, Y, P, and Sr may also be 0%. On the other hand, La, Ce, B, Y, P, and Sr contribute to the improvement of the end face corrosion resistance. Therefore, the concentration of each of La, Ce, B, Y, P, and Sr may also be set to 0.10% or more, 0.15% or more, or 0.20% or more. On the other hand, if the concentration of La, Ce, B, Y, P, and Sr is excessive, the planar corrosion resistance deteriorates. Therefore, the concentration of each of La, Ce, B, Y, P, and Sr is set to 0.5% or less. The concentration of each of La, Ce, B, Y, P, and Sr may also be set to 0.4% or less, 0.3% or less.

[0088] <Co, Bi, In, V, W: 0 to 0.5% respectively>

[0089] The concentration of each of Co, Bi, In, V, and W may also be 0%. On the other hand, Co, Bi, In, V, and W contribute to the improvement of the end face corrosion resistance. Therefore, the concentration of each of Co, Bi, In, V, and W may also be set to 0.10% or more, 0.15% or more, or 0.20% or more. On the other hand, if the concentration of Co, Bi, In, V, and W is excessive, the planar corrosion resistance deteriorates. Therefore, the concentration of each of Co, Bi, In, V, and W is set to 0.5% or less. The concentration of each of Co, Bi, In, V, and W may also be set to 0.4% or less, 0.3% or less.

[0090] <The remainder: Zn and impurities>

[0091] The remainder of the composition of the coating layer of the present embodiment is Zn and impurities. Zn is an element that gives the coating layer planar corrosion resistance and end face corrosion resistance. Impurities refer to components contained in the raw materials or components mixed in during the manufacturing process. For example, in the coating layer, it is possible that in addition to Fe, other components are also slightly mixed as impurities through the mutual atomic diffusion between the base steel plate and the plating bath.

[0092] The chemical composition of the coating layer is measured by the following method. First, the coating layer is stripped and dissolved using an acid containing an inhibitor that inhibits the corrosion of the steel plate to obtain an acid solution. Then, the obtained acid solution is subjected to inductively coupled plasma (ICP) analysis. Thereby, the chemical composition of the coating layer can be obtained. The type of acid is not particularly limited as long as it can dissolve the coating layer. It should be noted that the chemical composition measured by the above means is the average chemical composition of the entire coating layer.

[0093] Next, the metal structure of the coating layer will be described.

[0094] On the surface of the plating layer of this embodiment, a Mg2Si phase with a major diameter of 2 μm or more is exposed. The number density of the Mg2Si phase on the surface is 2 The number of the Mg2Si phases is 3 to 150. The Mg2Si phase is exposed on the surface of the coating, so that in the early stage of corrosion of the coating, the Mg2Si phase is corroded to form corrosion products, and the corrosion resistance of the end face of the steel plate is improved by the corrosion products. Thus, the end face corrosion resistance can be improved without damaging the plane corrosion resistance of the coating.

[0095] An electron beam microanalyzer (EPMA) is used to determine the Mg2Si phase at the surface of the coating. The surface of the coating is observed using a scanning electron microscope attached to the EPMA to determine the intermetallic compound of the analysis object. Then, by performing elemental analysis on the determined intermetallic compound, it is determined whether the intermetallic compound is a Mg2Si phase. Regarding the determination of the Mg2Si phase, an intermetallic compound containing more than 55 atomic % of Mg and more than 30 atomic % of Si is considered a Mg2Si phase. In addition to Mg and Si, the Mg2Si phase may also contain Ca, Zn, and Sn in a range of less than 10 atomic %, respectively.

[0096] The shape of the Mg2Si phase needs to have a major diameter of 2 μm or more, and is more preferably a needle-shaped phase with a major diameter of 2 μm or more. Furthermore, the aspect ratio is more preferably 2 or more. By setting the shape of the Mg2Si phase to have a major diameter of 2 μm or more, the Mg2Si phase becomes easily dissolved in the early stage of corrosion, and more corrosion products can be supplied to the end face of the steel plate, which can improve the end face corrosion resistance.

[0097] The major axis of the Mg2Si phase is set to the maximum length of the Mg2Si phase when the Mg2Si phase is observed with a scanning electron microscope. The aspect ratio is the ratio of the major axis to the minor axis (major axis / minor axis). The minor axis is the length in the direction orthogonal to the direction of the major axis, and more specifically, is set to the maximum length within the range of ±5° relative to the orthogonal direction of the major axis.

[0098] The number density of the Mg2Si phase at the surface is set to 10000 μm 2 3 to 150. Number density is less than 3 (pieces / 10000μm 2 ), the Mg2Si phase is too small and the end surface corrosion resistance becomes insufficient. On the other hand, even if the number density of the Mg2Si phase exceeds 150 (pieces / 10000 μm 2 ), the effect of improving the end surface corrosion resistance is also saturated, so 150 (pieces / 10000μm 2 ) is set as the upper limit. When the unit is set to (pieces / 10000μm 2), the number density of the Mg2Si phase may be greater than 15, or greater than 30. In addition, the number density of the Mg2Si phase may be less than 120, less than 100, less than 70, less than 50, or less than 30.

[0099] The number density of the Mg2Si phase at the surface of the coating may be affected by the average chemical composition of the coating. When the chemical composition of the coating is Mg: 4.5-8 mass % and Si: 0.1-2 mass %, the number density of the Mg2Si phase with a long diameter of 2 μm or more exposed on the surface of the coating may be 10000 μm. 2 The area is 15 to 150.

[0100] In addition, when the chemical composition of Al, Mg and Si in the coating layer is Al: 15-25 mass %, Mg: 4.5-8 mass %, Si: 0.1-2 mass %, the number density of the Mg2Si phase with a long diameter of 2 μm or more exposed on the surface of the coating layer can be per 10000 μm 2 The area is 30 to 150.

[0101] Next, on the surface of the plating layer of this embodiment, a Mg-Si-Zn-Al phase with a major diameter of 2 μm or more may be exposed. The number density of the Mg-Si-Zn-Al phase on the surface is preferably 10000 μm 2 5 to 150. If the Mg-Si-Zn-Al phase is exposed on the surface of the plating layer, the Mg-Si-Zn-Al phase is corroded at the initial stage of corrosion of the plating layer, thereby forming a dense corrosion product from Mg, Si, Zn, and Al. By forming this corrosion product, the flat corrosion resistance of the plating layer is further improved.

[0102] An electron beam microanalyzer (EPMA) is used to identify the Mg-Si-Zn-Al phase in the coating. The surface of the coating is observed using a scanning electron microscope attached to the EPMA to identify the intermetallic compound to be analyzed. Then, elemental analysis is performed on the identified intermetallic compound to determine whether the intermetallic compound is a Mg-Si-Zn-Al phase. Regarding the identification of the Mg-Si-Zn-Al phase, an intermetallic compound containing Mg: 20 to 45 atomic %, Si: 15 to 40 atomic %, Zn: 15 to 40 atomic %, and Al: 5 to 20 atomic % is defined as a Mg-Si-Zn-Al phase.

[0103] The number density of the Mg-Si-Zn-Al phase at the surface of the coating is affected by the average chemical composition of the coating. 2The number of Al, Mg and Si in the chemical composition of the plating layer is preferably 5 to 150, and Al: 15 to 25 mass %, Mg: 4.5 to 8 mass %, and Si: 0.1 to 2 mass %.

[0104] The shape of the Mg-Si-Zn-Al phase preferably has a long diameter of 2 μm or more, and more preferably a needle shape with a long diameter of 2 μm or more. Furthermore, the aspect ratio is preferably greater than 2. By setting the shape of the Mg2Si phase to a shape with a long diameter of 2 μm or more, the Mg-Si-Zn-Al phase becomes easily dissolved in the early stage of corrosion, more dense corrosion products can be formed, and the flat corrosion resistance can be improved.

[0105] The major axis of the Mg-Si-Zn-Al phase is set to the maximum length of the Mg-Si-Zn-Al phase when the Mg-Si-Zn-Al phase is observed with an electron microscope. The aspect ratio is the ratio of the major axis to the minor axis (major axis / minor axis). The minor axis is the length in the direction orthogonal to the direction of the major axis, and more specifically, is set to the maximum length within the range of ±5° relative to the orthogonal direction of the major axis.

[0106] The number density of the Mg-Si-Zn-Al phase at the surface is preferably 2 The number density is set to 5 (pieces / 10000 μm 2 ) or more, the flat corrosion resistance can be further improved. On the other hand, even if the number density of the Mg-Si-Zn-Al phase exceeds 150 ( / 10000 μm 2 ), the effect of improving the flat corrosion resistance is also saturated, so 150 (pieces / 10000μm 2 ) is set as the upper limit. When the unit is set to (pieces / 10000μm 2 ), the number density of the Mg-Si-Zn-Al phase may be greater than 10, or greater than 15. In addition, the number density of the Mg-Si-Zn-Al phase may be less than 120, less than 100, less than 80, less than 70, less than 50, or less than 30.

[0107] It should be noted that the Mg-Si-Zn-Al phase can also be 2 An area greater than 0 and a number density less than 5 exist on the surface of the coating.

[0108] The method for measuring the number density of the Mg2Si phase and the Mg-Si-Zn-Al phase is described. A 50μm square measurement area is set on the surface of the coating. The measurement area is set to 8 locations, and 8 measurement areas are randomly configured on the surface of the coating. The measurement areas are separated in a non-overlapping manner. The intermetallic compound is confirmed by observing the set measurement area with a scanning electron microscope. Then, the composition of the intermetallic compound is analyzed by EPMA to distinguish the Mg2Si phase and the Mg-Si-Zn-Al phase. Furthermore, the number of Mg2Si phases and Mg-Si-Zn-Al phases in each measurement area is measured. The measurement conditions of EPMA are set, for example, as follows: the acceleration voltage is 15kV, the current is 0.05μA, and the irradiation time is 50ms. As EPMA, for example, JXA-8230 made by JEOL Ltd. is used.

[0109] When the Mg2Si phase and the Mg-Si-Zn-Al phase are needle-shaped, it is possible that part of the phase is within the measurement area and the rest of the phase is outside the measurement area, but such phases are also included in the number of measurement objects.

[0110] In addition, when the Mg2Si phase and the Mg-Si-Zn-Al phase are needle-shaped, multiple Mg2Si phases or multiple Mg-Si-Zn-Al phases may overlap each other. In such a case, when the major axis directions of the phases overlap in different directions, the overlapping phases are measured as the number of phases. For example, when two Mg2Si phases overlap each other and their major axis directions are in different directions, the number is counted as 2.

[0111] Then, based on the number of Mg2Si phases with a long diameter of 2 μm or more and the number of Mg-Si-Zn-Al phases with a long diameter of 2 μm or more measured in the 8 measurement areas and the total area of ​​the measurement areas, the number of phases per 10000 μm was calculated. 2 The number of is taken as the number density.

[0112] In addition, when the coating contains 0.05 to 0.5 mass % Sn, it is preferred that the coating contain Mg2Sn phase. Since the Mg2Sn phase is a small amount, its presence is detected and confirmed by X-ray diffraction measurement. By containing the Mg2Sn phase in the coating, the corrosion resistance of the end face of the coating is further improved. Whether the coating contains the Mg2Sn phase is determined by whether a diffraction peak unique to Mg2Sn appears. Here, the diffraction peak unique to Mg2Sn refers to a peak that appears at a diffraction angle 2θ of 23.4 ± 0.3 degrees.

[0113] The coating weight per single side of the plating layer is set to, for example, 20 to 150 g / m 2By setting the adhesion amount per single side to 20g / m 2 The above can further improve the flat corrosion resistance and end surface corrosion resistance of the plated steel sheet. On the other hand, by setting the coating amount per single surface to 150 g / m 2 Next, the workability of the plated steel sheet can be further improved.

[0114] Next, a method for producing a plated steel sheet according to the present embodiment will be described, but the method for producing a plated steel sheet according to the present embodiment is not particularly limited. For example, the plated steel sheet according to the present embodiment can be obtained according to the production conditions described below.

[0115] The manufacturing method of the plated steel sheet of the present embodiment is to anneal the steel sheet with adjusted surface roughness in a reducing atmosphere, immerse the steel sheet just after annealing in a hot dip coating bath and then pick it up, thereby forming a coating on the surface of the steel sheet. Next, cooling gas is blown during the period from the bath temperature to the coating temperature below 300°C to cool it. Regarding the gas flow when blowing the cooling gas, the gas flow from the bath temperature to the controlled cooling temperature (the gas flow rate in the temperature range above the controlled cooling temperature and below the bath temperature) is set to 100 to 5000 L / min / m 2 The gas flow rate (gas flow rate in the temperature range above the cooling stop temperature and below the controlled cooling temperature) from the controlled cooling temperature to the cooling stop temperature (300°C or less in the present embodiment) is set to 10000 to 80000 L / min / m 2 range.

[0116] The controlled cooling temperature is set to a temperature within a range of -10°C to -80°C relative to the crystallization temperature of the Mg2Si phase.

[0117] Regarding the roughness of the surface of the steel sheet to be plated, the length L of the roughness curve per reference length L0 is p The ratio (L p / L0) is set to 1.0 or more, and the arithmetic mean roughness Ra is set to 0.1 μm or more. If it is out of this range, a large amount of Mg2Si phase may be crystallized near the interface between the coating and the steel sheet, and the number density of the Mg2Si phase at the surface of the coating is reduced. (L p The upper limit of the arithmetic mean roughness Ra is preferably 3.0 or less, and may be 2.5 or less, or 2.0 or less. The upper limit of the arithmetic mean roughness Ra is preferably 4.0 μm or less, and may be 3.5 μm or less. There is no particular limitation on the adjustment of the roughness of the steel plate surface, but it can be adjusted, for example, by rolling the plated original plate with a roller or a roller for temper rolling whose roller surface is adjusted to the desired roughness to transfer the surface shape of the roller. In addition, it can also be adjusted by pickling.

[0118] (L p / L0) and arithmetic mean roughness are measured, for example, using a shape measurement laser microscope (model: VK-8700) manufactured by KEYENCE Co., Ltd. The measurement conditions are, for example, set to measurement mode: laser confocal, measurement quality: high precision, spacing: 0.75 μm, double scanning: open, optical zoom: 1x, objective lens name: plan achromat (Plan), γ coefficient: 0.45, bias: 0%, and the measurement is performed. It should be noted that (L p The measuring device used in the measurement of (L / L0) and arithmetic mean roughness is not limited to the above example. The roughness curve is obtained by sequentially applying the profile curve filters with cutoff values ​​λc and λs to the cross-sectional curve obtained by measurement in accordance with JIS B 0601:2013. Specifically, the components with wavelength λc of 0.001 mm or less and the components with wavelength λs of 0.2 mm or more are removed from the obtained measurement results to obtain the roughness curve. Based on the obtained roughness curve, (L p / L0) and arithmetic mean roughness.

[0119] Annealing of the steel sheet to be plated is performed in a reducing atmosphere. The reducing atmosphere and annealing conditions are not particularly limited. Through this annealing, oxides present on the surface of the steel sheet are removed as much as possible.

[0120] Next, the steel sheet immediately after annealing is immersed in a hot dip coating bath. The chemical composition of the hot dip coating bath may be appropriately adjusted so as to obtain the chemical composition of the coating layer described above. In addition, the temperature of the hot dip coating bath is not particularly limited, and a temperature at which hot dip coating can be performed may be appropriately selected. For example, the coating bath temperature may be set to a value that is about 20° C. higher than the melting point of the coating bath.

[0121] Next, the steel sheet is scooped out of the hot dip coating bath. By controlling the scooping speed of the steel sheet, the amount of the coating can be controlled. If necessary, the amount of the coating can be controlled by wiping the steel sheet with the coating. The amount of the coating is not particularly limited, and can be set within the above range, for example.

[0122] Next, the coating is cooled. The cooling is performed by blowing cooling gas on the steel sheet just after being taken out of the hot dip coating bath. The cooling by blowing cooling gas is performed continuously during the period when the temperature of the steel sheet increases from the bath temperature to 300°C. The cooling conditions below 300°C are not particularly limited, and cooling by blowing cooling gas or natural cooling may be performed next.

[0123] In the cooling by blowing cooling gas, it is carried out by configuring a cooling belt along the conveying path of the steel plate. In the cooling belt, there are multiple blowing nozzles for cooling gas. The shape of the gas nozzle that sprays the cooling gas is set to a diameter range of 1 to 50 mm, for example. The angle between the front end of the gas nozzle and the steel plate is set to a range of 70 to 110°, more preferably 90° (right angle). The distance between the front end of the gas nozzle and the steel plate is set to a range of 30 to 1000 mm. It should be noted that the shape, angle, and distance of the gas nozzle are simply an example and are not limited to the above range.

[0124] The cooling gas to be blown is not particularly limited, and may be a non-oxidizing gas such as nitrogen, an inert gas such as argon, or air, or a mixed gas thereof.

[0125] In this embodiment, the gas flow when blowing the cooling gas is controlled in two stages. That is, based on the temperature of the steel plate, the gas flow from the coating bath temperature to the controlled cooling temperature (a temperature in the range of -10 to -80°C relative to the crystallization temperature of the Mg2Si phase) is set to 100 to 5000 L / min / m 2 The range is preferably set to 500 to 5000 L / min / m 2 The gas flow rate from the controlled cooling temperature to below 300°C is set to 10000-80000 L / min / m 2 The controlled cooling temperature is a temperature presumed to be the crystallization start temperature of the Mg2Si phase.

[0126] When the gas flow is set to 5000L / min / m 2 When the gas flow rate is set to 10000 L / min / m 2 In the case of the above range, vibration can be applied to the steel plate being cooled.

[0127] Furthermore, by setting the gas flow from the coating bath temperature to the controlled cooling temperature to 100 to 5000 L / min / m 2 The range is preferably set to 500 to 5000 L / min / m 2 The range of , thereby promoting the nucleation of Si-containing phases other than Mg2Si phase without vibrating the steel plate, so that Mg and Si are concentrated in the unsolidified liquid phase. Next, the gas flow is set to 10000-80000 L / min / m from the controlled cooling temperature to below 300°C. 2The range of the gas flow is within the above range, so that the surface of the unsolidified liquid phase can be vibrated to crystallize a large amount of Mg2Si phase on the surface of the coating. If the range of the gas flow is out of the above range, it becomes difficult to crystallize a large amount of Mg2Si phase on the surface of the coating.

[0128] The crystallization temperature of the Mg2Si phase changes according to the chemical composition of the coating, so it is calculated using a calculation state diagram. Specifically, the thermodynamic data of the intermetallic compound phase, the metal phase, etc. that can be contained in the Al-Mg-Zn alloy are concentrated to construct a calculation state diagram database, and the Mg2Si phase crystallization temperature is calculated for each chemical composition of the coating by using the CALPHAD method (phase diagram calculation; CALculation of PHAseDiagram) method. More specifically, by using the thermodynamic equilibrium calculation software "Thermo-Calc" ((Thermo-Calc is a registered trademark) Thermo-Calc Software Company), the Mg2Si phase crystallization temperature can be estimated. It should be noted that the thermodynamic equilibrium calculation software used in the calculation is not limited to "Thermo-Calc" (registered trademark), and other software can also be used. The temperature in the range of -10 to -80°C relative to the obtained Mg2Si phase crystallization temperature is used as the controlled cooling temperature.

[0129] In the above-mentioned manufacturing method, by pre-adjusting the surface roughness of the steel sheet surface, the nucleation of the Mg2Si phase can be suppressed, thereby suppressing the crystallization of the Mg2Si phase near the interface between the coating and the steel sheet. By hot-dip coating such a steel sheet and controlling the cooling conditions after coating as described above, a large amount of Mg2Si phase is crystallized on the surface of the coating. It is estimated that a large amount of Mg2Si phase with a long diameter of 2 μm or more can be formed on the surface of the coating.

[0130] It should be noted that as long as the necessary conditions shown in the present invention are met, the method for manufacturing the plated steel sheet is not limited to the above content, and instead of the hot dip method, electroplating, vapor deposition plating, spraying, cold spraying, etc. can also be used.

[0131] Example

[0132] The following is an explanation of the embodiments of the present invention. However, the conditions in the embodiments are only a condition example adopted to confirm the feasibility and effect of the present invention. The present invention is not limited to this condition example. As long as it does not deviate from the main purpose of the present invention and achieves the purpose of the present invention, the present invention can adopt various conditions.

[0133] For the plated original plate, a cold-rolled steel plate (0.05C-0.1Si-0.2Mn) with a plate thickness of 2.3 mm is used. The surface roughness of a portion of the plated original plate is controlled using a skin-pass rolling mill, etc. The steel plate with adjusted surface roughness is annealed. The annealed steel plate is dipped in various hot-dip baths and then picked up, so that a coating is attached to the surface of the steel plate. Then, various plated steel plates are manufactured by cooling with a cooling gas from the time the steel plate is just picked up from the plating bath until the coating reaches 300°C.

[0134] The surface roughness of the steel sheet surface to be plated is calculated by calculating the length L of the roughness curve per reference length L0. p The ratio (L p / L0) is set to 1.1 to 2.7, and the arithmetic mean roughness Ra is set to the range of 0.5 to 3.7 μm.

[0135] (L p The measurement of the surface roughness (L / L0) and the arithmetic mean roughness was performed using a shape measurement laser microscope (model: VK-8700) manufactured by KEYENCE Co., Ltd. The measurement conditions were set as follows: measurement mode: laser confocal, measurement quality: high precision, pitch: 0.75 μm, double scanning: open, optical zoom: 1x, objective lens name: plan achromat (Plan), γ coefficient: 0.45, bias: 0%, and the measurement was performed.

[0136] Regarding the annealing conditions when the steel sheet is annealed in a reducing atmosphere, the soaking temperature is set to 600°C and the soaking time is set to 10 seconds. The annealing atmosphere is set to a reducing atmosphere of a mixed gas containing 5% hydrogen and the remainder nitrogen. Then, the annealed steel sheet is air-cooled with nitrogen until the dip plate temperature reaches the bath temperature + 20°C, and then dipped in the hot dip bath and pulled out. The pulling out speed is set to 20 to 200 mm / second.

[0137] The chemical composition of the plating layer is shown in Table 1. The manufacturing conditions were set as shown in Table 2. In addition, the metal structure of the plating layer was evaluated, and the results are shown in Table 3. Furthermore, the plane corrosion resistance and the end surface corrosion resistance of the plated steel sheet were evaluated, and the results are shown in Table 3.

[0138] The chemical composition of the coating and the evaluation of the metal structure of the coating are carried out by the above-mentioned means. It should be noted that, with respect to the Mg2Si phase, the one with a major diameter of 2 μm or more is taken as the measurement object. In addition, with respect to the Mg-Si-Zn-Al phase, the one with a major diameter of 2 μm or more is taken as the measurement object. The aspect ratio of the measured Mg2Si phase and Mg-Si-Zn-Al phase is 2 or more.

[0139] The evaluation of plane corrosion resistance is set as follows. The obtained hot-dip galvanized steel material is cut into 100 mm × 50 mm and provided for the plane corrosion resistance evaluation test. The evaluation of plane corrosion resistance is carried out by the corrosion promotion test specified in JASO-CCT-M609, and is carried out by comparing the corrosion loss after 120 cycles. The evaluation criteria are set as follows, and "AAA", "AA" and "A" are set as qualified.

[0140] AAA: Corrosion loss less than 50g / m 2

[0141] AA: Corrosion loss is 50g / m 2 Above and below 90g / m 2

[0142] A: Corrosion loss is 90g / m 2 Above and below 120g / m 2

[0143] B: Corrosion loss is 120g / m 2 above

[0144] Regarding the end surface corrosion resistance, the plated steel sheet was cut at an arbitrary position to expose the cut end surface, and the cut end surface was subjected to the neutral salt water spray test specified in JIS Z 2371. Evaluation was performed based on the red rust generation condition of the cut end surface. The evaluation criteria for the red rust area ratio are shown below. "AAA", "AA" and "A" are set as acceptable.

[0145] AAA: Red rust area rate is less than 10% at 2500h

[0146] AA: Red rust area rate is less than 10% at 2000h

[0147] A: After 1500h, the red rust area rate is less than 20%

[0148] B: At 1500h, the red rust area rate exceeds 20%

[0149] As shown in Tables 1 to 3, Examples 1 to 30 and 39 of the present invention, in which the chemical composition and metal structure of the plating layer are appropriately controlled, have excellent both flat corrosion resistance and end surface corrosion resistance. It should be noted that the coating weight per single surface of the example is 20 to 150 g / m 2 range.

[0150] In Comparative Example 31, the Al content of the plating layer was insufficient. Therefore, in Comparative Example 31, Si was not crystallized as a Mg2Si phase but was crystallized as a Si phase, and the flat corrosion resistance was insufficient.

[0151] In Comparative Example 32, the amount of Al in the coating is excessive. Therefore, in Comparative Example 32, a Fe-Al-Si based interface alloy layer is formed at the interface between the coating and the steel sheet, and at this time, Si is consumed by the formation of the interface alloy layer, and no Mg2Si phase is crystallized on the surface, and the end face corrosion resistance is reduced.

[0152] In Comparative Example 33, the Mg content of the plating layer was insufficient. Therefore, in Comparative Example 33, Si was not crystallized as a Mg2Si phase but was crystallized as a Si phase, and the flat surface corrosion resistance and the end surface corrosion resistance were reduced.

[0153] In Comparative Example 34, the amount of Mg in the plating layer was excessive. Therefore, in Comparative Example 34, the nucleation of the Mg2Si phase progressed inside the plating layer, and the Mg2Si phase did not crystallize on the surface, resulting in reduced flat corrosion resistance.

[0154] In Comparative Example 35, the Si content of the plating layer was excessive. Therefore, in Comparative Example 35, the nucleation of the Mg2Si phase progressed inside the plating layer, and the Mg2Si phase did not crystallize on the surface, resulting in reduced flat corrosion resistance and end surface corrosion resistance.

[0155] In Comparative Example 36, the amount of Ca in the plating layer was excessive. Therefore, in Comparative Example 36, a large amount of Ca-containing compounds were generated, and the Mg2Si phase was not crystallized, so that the flat surface corrosion resistance and the end surface corrosion resistance were reduced.

[0156] In Comparative Example 37, the cooling gas flow from the bath temperature to the controlled cooling temperature was excessive. Therefore, in Comparative Example 37, the nucleation of the Mg2Si phase progressed inside the coating, and the Mg2Si phase did not crystallize on the surface, resulting in reduced flat corrosion resistance and end surface corrosion resistance.

[0157] In Comparative Example 38, the cooling gas flow was insufficient from the control cooling temperature to 300° C. Therefore, in Comparative Example 38, the nucleation of the Mg2Si phase progressed inside the coating, and the Mg2Si phase did not crystallize on the surface, resulting in reduced flat corrosion resistance and end surface corrosion resistance.

[0158] [Table 1]

[0159]

[0160] The underlined part indicates that it is outside the scope of the present invention.

[0161] [Table 2]

[0162]

[0163] The underlined portion indicates that the conditions are outside the range of the preferred production conditions.

[0164] [Table 3]

[0165]

[0166] The underlined part indicates that it is outside the scope of the present invention.

[0167] Industrial Applicability

[0168] The plated steel sheet of the present disclosure is excellent in both flat surface corrosion resistance and coating adhesion, and therefore has high industrial applicability.

[0169] Explanation of symbols

[0170] 1 coated steel plate, 11 steel plate, 12 coating.

Claims

1. A plated steel sheet, characterized in that: The invention comprises a steel plate and a plating layer arranged on the surface of the steel plate. The chemical composition of the coating contains, in mass %, Al:10.0~25.0%、 Mg: 3.0-10.0%, Fe: 0.01-2.0%, Si: more than 0% and 2.0% or less, further comprising one or more selected from the following Group A, Group B, and Group C, The remainder contains Zn and impurities. The number density of the Mg2Si phase with a major diameter of 2 μm or more exposed on the surface of the plating layer is 2 The area is 3 to 150. [Group A]Ni: 0~1.0% [Group B] Ca: 0~0.05% [Group C] One or more of Sb: 0-0.5%, Pb: 0-0.5%, Cu: 0-1.0%, Sn: 0-1.0%, Ti: 0-1.0%, Cr: 0-1.0%, Nb: 0-1.0%, Zr: 0-1.0%, Mn: 0-1.0%, Mo: 0-1.0%, Ag: 0-1.0%, Li: 0-1.0%, La: 0-0.5%, Ce: 0-0.5%, B: 0-0.5%, Y: 0-0.5%, P: 0-0.5%, Sr: 0-0.5%, Co: 0-0.5%, Bi: 0-0.5%, In: 0-0.5%, V: 0-0.5%, W: 0-0.5%: 0-5% in total.

2. The plated steel sheet according to claim 1, wherein: The chemical composition of the plating layer includes Mg: 4.5-8 mass %, Si: 0.1-2 mass %, The number density of the Mg2Si phase with a major diameter of 2 μm or more exposed on the surface of the plating layer is 2 The area is 15 to 150.

3. The plated steel sheet according to claim 1, wherein: The chemical composition of Al, Mg and Si in the plating layer is Al: 15-25 mass %, Mg: 4.5-8 mass %, Si: 0.1-2 mass %, The number density of the Mg2Si phase with a major diameter of 2 μm or more exposed on the surface of the plating layer is 2 The area is 30 to 150.

4. The plated steel sheet according to any one of claims 1 to 3, wherein The chemical composition of Al, Mg and Si in the plating layer is Al: 15-25 mass %, Mg: 4.5-8 mass %, Si: 0.1-2 mass %, The number density of the Mg-Si-Zn-Al phase with a major diameter of 2 μm or more exposed on the surface of the plating layer is 2 The area is 5 to 150.

5. The plated steel sheet according to any one of claims 1 to 3, wherein The chemical composition of the plating layer is Sn: 0.05-0.5 mass%, In an X-ray diffraction measurement of the coating, a Mg2Sn phase was detected in the coating.

6. The plated steel sheet according to claim 4, wherein: The chemical composition of the plating layer is Sn: 0.05-0.5 mass%, In an X-ray diffraction measurement of the coating, a Mg2Sn phase was detected in the coating.

7. The plated steel sheet according to claim 1, wherein: The plating layer has a chemical composition containing the group A in mass %.

8. The plated steel sheet according to claim 1, wherein The plating layer has a chemical composition containing the B group in mass %.

9. The plated steel sheet according to claim 1, wherein: The plating layer has a chemical composition containing the C group in mass %.

Citation Information

Patent Citations

  • MOLTEN Al-Zn-Mg-Si PLATED SHEET STEEL AND PRODUCTION METHOD THEREOF

    JP2016166414A

  • Flexible Display Device

    JP2022100351A

  • Plated steel

    WO2018139619A1

  • Plated steel

    WO2018139620A1

  • High-corrosion-resistance hot-dip galvanized steel plate having highly uniform appearance and manufacturing method therefor

    CN103620079A